Southern Gondwanan Late Jurassic continental teleosts (Actinopterygii, Teleostei): phylogeny and biogeography - Sferco, E. (2010)
During the Jurassic the teleost fishes went through their first important radiation and colonization of continental environments. Due to a bias in the geological record, Jurassic fresh-water deposits are very scarce, and only three continental fish faunas of Late Jurassic age are known worldwide: the Almada Fauna from the Cañadón Calcáreo Formation in central Chubut, Argentina, the Talbragar Fauna from the Australian Talbragar Beds and the fish assemblages from the Morrison Formation in USA. The Almada and Talbragar faunas show strong similarities. Regarding their taxonomic composition, both faunas share one genus of coccolepid and the presence of halecomorphs and basal teleosts. Concerning their geological settings and taphonomic background, each fauna occur in a single horizon within the stratigraphic column, representing mass mortality events, probably related to volcanic activity. To date, the Almada Fauna includes two species of teleosts: "Tharrias" feruglioi (Bordas) and Luisiella inexcutata Bocchino. Interestingly, "T". feruglioi shares very similar morphological features with Cavenderichthys talbragarensis (Woodward), the only valid species of teleost from Talbragar. A previous phylogenetic analysis showed a sister group relationship between these two species. Strengthening the resemblance between the Almada and Talbragar faunas, this result suggested close biogeographic relationships between the Argentinean and Australian localities. Here we present a new phylogenetic analysis including other taxa of fresh-water teleosts and new characters, the results of which support this hypothesis of close biogeographic connection.